Kuna can't hold back the tears after bagging kumite gold - The Star, (2012)
PUTRAJAVA: Former Asian Games silver medallist L. Kunasilan was teary-eyed after bagging the men's kumite below 60kg gold medal in the National Karate Championships in Putrajaya.